Palamba, Widsri ANALISIS KINERJA OPERASI MIKROTRANS JAK LINGKO (STUDI KASUS: RUTE GROGOL-MERUYA) - Widsri Palamba (UKI Press, 2025)
One of the forms of public transportation management in the JakLingko program in the DKI Jakarta region is improving the quality of service and operational efficiency of microtrans. This is necessary due to reports of poor or unpleasant passenger experiences through complaints on social media. These complaints include passenger discomfort, vehicles driving at high speeds, unstable travel times, and other issues. Therefore, research was conducted to maximize the JakLingko microtrans service for the residents of DKI Jakarta. The operational performance analysis is based on operational efficiency, reviewing factors such as vehicle load, fleet availability, average headway, average travel time along the route, and average speed at specific times within the research constraints. The operational performance analysis of JakLingko microtrans will provide information for service improvement planning, which is closely related to passenger safety and security. Data collection was carried out on the Grogol–Meruya route, which is approximately 18.2 km long. This route is located in West Jakarta, with a total of 70 bus stops spread along the transportation route. Minimum service standards can be used to measure the quality of public transportation services, serving as a benchmark for public transportation service guidelines in Indonesia. The reference indicators in this research are based on the Directorate General of Land Transportation in 2002. The results of the transportation performance analysis show a load factor below 70%, specifically 65.01%, an average headway of 3.43 minutes, an average waiting time of 1.72 minutes, an average travel time of 5.21 minutes/km, and an average speed of 11.31 km/h. Overall, there are still several areas that need improvement, such as increasing the efficiency of headway based on studies of uneven passenger distribution and adjusting service frequency to be more regular based on operational hours. Keywords: Performance; operational; microtrans